PENYEBARAN TAREKAT SAMMANIYAH DI KALIMANTAN SELATAN OLEH K.H.MUHAMMAD ZAINI GHANI - Mubarak, Ahmad Zakki (Pascasarjana UIN ANTASARI Banjarmasin, 2011)
This paper describes about the al-Sammaniyah tarekat which was popularized by K.H. Muhammad Zaini. He is known as a scholar who became a role model of Banjar society. K.H. Muhammad Zaini is a charismatic cleric (ulama). His popularity is not only in the Kalimantan region, but to foreign countries. Pilgrims who follow the teachings amount to dozens, even thousands of people. He is known for its breadth of his knowledge, moral virtue, and generosity. In delivering his message, he has a quiet way of speaking, so that the people who listens him feel cool, calm and solemn.